After the prophet : the epic story of the Shia-Sunni split in Islam - Hazleton, Lesley, 1945- (New York : Anchor Books, 2010)
Balancing past and present, Hazelton shows how 7th-century events are alive in Middle Eastern hearts and minds today as though they had just happened, shaping modern headlines from Iran's Islamic Revolution to the civil war in Iraq.
Muhammad -- Ali -- Hussein.
Includes bibliographical references (pages 215-230) and index.
Keywords: Islam -- History; Caliphate -- History; c; ?A'ishah, -- approximately 614-678.; ?Ali ibn Abi ?alib, -- Caliph, -- approximately 600-661.; Shi?ah -- Relations -- Sunnites; Sunnites -- Relations -- Shi?ah.